Decision Support System for Regional Planning of Horticultural Commodities Using the CODAS Method Based on a Case Study - Indra Irawan; Dio Arif Hanafi Harianja; Armansyah Putra Siregar; Muhammad Angga Septiawan; M Rizky Ramadhan; Mutammim Zisdian (Ali Institute or Research and Publication, 2026)
This study aims to determine the priority of regional development for horticultural commodities. The planning and selection process involves various criteria, including productivity, land area, selling price, market demand, resistance to pests and climate, production costs, and government support; therefore, a systematic and objective approach is required. This study employs the Combinative Distance-Based Assessment (CODAS) method, a Multi-Criteria Decision Making (MCDM) approach that evaluates alternatives based on their Euclidean distance from the negative-ideal solution. The data used are secondary data obtained from the Department of Food Security, Food Crops, and Horticulture of North Sumatra Province and the Central Statistics Agency (BPS), complemented by literature review, observation, and interviews, and then analyzed quantitatively. The results show that bananas rank first with a Euclidean distance value of 0.209949, followed by cayenne pepper with 0.165406 and papaya with 0.161221. Furthermore, red chili (0.156669) and shallots (0.126977) also exhibit relatively high values compared to other commodities. A higher Euclidean distance indicates greater potential for development in regional horticultural planning. This study provides a priority ranking of commodities that can serve as a basis for decision-making in regional horticultural development planning in North Sumatra Province.